On bg**- Connected Spaces - Ibraheem, AfrahM. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, we define the bg**-connected space and study the relation between this space and other kinds of connected spaces .Also we study some types of continuous functions and study the relation among (connected space, b-connected space,  bg-connected  space and bg**-connected space) under these types of continuous functions.